Determination of Pesticide Residues in Food Premises Using QuECHERS Method in Bench-Sheko Zone, Southwest Ethiopia. (20th March 2021) - Mekonnen, Besufekad; Siraj, Jafer; Negash, Samuel
Abstract : Pesticides are risk factors in human life causing chronic human health effects. They are commonly used across the globe to enhance human endeavors. In Ethiopia, pesticides are widely used by local farmers and governmental organizations for pest control purpose. Pesticide residues in food items have been a concern to the consumers and environment they live in. Therefore, this study was aimed at determining the amount of organochlorine and organophosphate pesticide residues in cereal crops in Bench-Sheko Zone, Ethiopia. A cross-sectional laboratory-based study design was employed to determine the amount of pesticide residues. The samples were extracted using a Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction and clean up method. Finally, the extracted samples were injected into gas chromatography tandem mass spectrometer and the types and concentrations of pesticide residues were analyzed. The highest concentration of endosulfan sulfate (0.076 mgkg -1 ) was detected in rice, followed by dimethoate (0.068 mgkg -1 ) and p, p ′ -DDE (0.087 mgkg -1 ) in sorghum and common millet, respectively, in the samples obtained from the Gurafarda site.The highest concentration of p, p ′ -DDT (0.133 mgkg -1 ) was detected in common millet, followed by aldrin (0.082 mgkg -1 ) and dimethoate (0.077 mgkg -1 ) in sorghum and common millet, respectively, in the samples obtained from the North Bench site. In addition, aldrin detected in rice, sorghum, and common millet obtained from the three sites was a residue of above the maximum residual limits set by Codex Alimentarius regulations and European Union. The finding shows that an indication of the widespread use of pesticides in cereal crops.